2008
DOI: 10.1243/09544070jauto755
|View full text |Cite
|
Sign up to set email alerts
|

A computational fluid dynamic analysis on the effect of front row pin geometry on the aerothermodynamic properties of a pin-vented brake disc

Abstract: Increasing demand from the consumer for higher levels of refinement from their passenger vehicles has put considerable pressure on the automotive industry to produce ever quieter cars. In order to prevent the occurrence of many forms of brake noise, especially judder and drone, excessive heating of the brake disc must be avoided, while minimizing temperature variations across the rotor. In order for this to be achieved the brake rotor must be designed such that it ensures sufficient uniform heat dissipation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 11 publications
3
18
0
Order By: Relevance
“…CFD analysis of the baseline disc unearthed many interesting fluid dynamic phenomena which have been included in the previous paper [6]. Some of the key results from the initial analysis included the identification of the position of maximum and minimum values of static pressure to be on the high-pressure and suction side of the leading edge of the pins in the front row.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…CFD analysis of the baseline disc unearthed many interesting fluid dynamic phenomena which have been included in the previous paper [6]. Some of the key results from the initial analysis included the identification of the position of maximum and minimum values of static pressure to be on the high-pressure and suction side of the leading edge of the pins in the front row.…”
Section: Resultsmentioning
confidence: 99%
“…A full description of the validation has been included in the paper by Palmer et al [6]. It has been shown that the numerical simulations match experimental data favourably both qualitatively and quantitatively and can be used with confidence for further flow analysis.…”
Section: Fig 2 Geometric Details Of the Baseline Discmentioning
confidence: 99%
See 3 more Smart Citations